CONTEXT IN PRAGMATICS - Indrawati, - (Language Circle: Journal of Language and Literature, 2009)
People carry out almost all social behaviors through language, either spoken or written. The language to be used needs rules and principles; and when it comes to see language from a socio-cultural perspective, and consider the ‘worlds of users’ incorporating the context or ‘human condition’, people refer to the pragmatic use of it, which means that Pragmatics is the study of a context-dependent language. People owe their respects to great many linguists and experts in Pragmatics for their various expertises in this field to explain ‘how the language operates in force of contextually implied conditions’. With this view, the writer of this paper attempts to learn the important relationship between context and Pragmatics.